Simulation of Leaf Area Development Based on Dry Matter Partitioning and Specific Leaf Area for Cut Chrysanthemum - LEE, J. H. (Ann Bot, 2003)
This work aims to predict time courses of leaf area index (LAI) based on dry matter partitioning into the leaves and on specific leaf area of newly formed leaf biomass (SLA(n)) for year‐round cut chrysanthemum crops. In five glasshouse experiments, each consisting of several plant densities and planted throughout the year, periodic destructive measurements were conducted to develop empirical models for partitioning and for SLA(n). Dry matter partitioning into leaves, calculated as incremental leaf dry mass divided by incremental shoot dry mass between two destructive harvests, could be described accurately (R(2) = 0·93) by a Gompertz function of relative time, R(t). R(t) is 0 at planting date, 1 at the start of short‐days, and 2 at final harvest. SLA(n), calculated as the slope of a linear regression between periodic measurements of leaf dry mass (LDM) and LAI, showed a significant linear increase with the inverse of the daily incident photosynthetically active radiation (incident PAR, MJ m(–2) d(–1)), averaged over the whole growing period, the average glasshouse temperature and plant density (R(2) = 0·74). The models were validated by two independent experiments and with data from three commercial growers, each with four planting dates. Measured shoot dry mass increase, initial LAI and LDM, plant density, daily temperature and incident PAR were input into the model. Dynamics of LDM and LAI were predicted accurately by the model, although in the last part of the cultivation LAI was often overestimated. The slope of the linear regression of simulated against measured LDM varied between 0·95 and 1·09. For LAI this slope varied between 1·01 and 1·12. The models presented in this study are important for the development of a photosynthesis‐driven crop growth model for cut chrysanthemum crops.